English Vocabulary Mastery In Vocational Higher Education: An Analysis Of Challenges And Feasible Strategies - Tian Havwini; Desi Ratnasari; Nurul Fadilah; Feby Feby; Fadli Firdaus (Departement of Mathematics Education, 2024)
Vocabulary mastery is one of the important keys that bridge the subject comprehension. Understanding new concepts, ideas, and principles requires knowledge and competence in using words in various settings. The success of English learning in ESP will then contribute to the success of understanding other subjects in the field. Therefore, this research aims to investigate the problems, needs, and feasible strategies in improving vocabulary mastery in vocational higher education settings. The total of 303 freshmen students participated in this study, along with 7 English lecturers who were teaching in their classes. A vocabulary test, open-ended questionnaire, and focus group discussion (FGDs) were used as instruments. The results present the current state of students’ vocabulary level. Moreover, a number of strategies were also recommended by the lecturer in terms of students’ English vocabulary learning dan development. Future research directions are also presented